2016
DOI: 10.5897/ajb2016.15445
|View full text |Cite
|
Sign up to set email alerts
|

Growth regulators, DNA content and anatomy in vitro-cultivated Curcuma longa seedlings

Abstract: Curcuma longa L., from the Zingiberaceae family, generally reproduces through its rhizomes, which are also utilized for therapeutic purposes because they are rich in terpenoids. Its conventional propagation has low efficiency due to the small number of seedlings and their contamination by pathogens. Therefore, this study aimed to evaluate the influence of growth regulators on the development of in vitro-cultivated C. longa as well as to determine their influence on DNA content and foliar anatomy. Shoots were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…In addition, there was an increase in the number of leaves (13.0) and the number of roots (7.0), which were double in number than those obtained the M2 medium (Table 3). We emphasize that this culture medium was also shown to be efficient for the development of explants in the studies by Antoniazzi et al (2016) and Ferrari et al (2016).…”
Section: Different Compositions Of Ms Mediummentioning
confidence: 76%
See 3 more Smart Citations
“…In addition, there was an increase in the number of leaves (13.0) and the number of roots (7.0), which were double in number than those obtained the M2 medium (Table 3). We emphasize that this culture medium was also shown to be efficient for the development of explants in the studies by Antoniazzi et al (2016) and Ferrari et al (2016).…”
Section: Different Compositions Of Ms Mediummentioning
confidence: 76%
“…Among the growth regulators, cytokinins and auxins are the most frequently used plant hormones in the in vitro culture medium, both of which may influence both plant morphology and physiological responses, as reported by Antoniazzi et al (2016). These authors showed, during their trials with C. longa, that the addition of auxins and cytokinins to the Murashige and Skoog (MS) medium increases the shoot fresh mass, as well as the number and dry mass of the roots.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…To remove excess paraplast, slides with the fixed tissue were then placed in a water bath containing butyl acetate to be dehydrated in butyl series ethanol. Slides were stained with safrablau and a blend of astra blue and safranin (9:1, v/v) (Bukatsch, 1972) followed by modification according to the method of Antoniazzi et al (2016). Finally, glass varnish was applied to ensure adherence of the coverslip (Paiva, 2006).…”
Section: Anatomical Analysismentioning
confidence: 99%